STUDY ON THE SITUATION OF NUTRITION IN CHILDREN FROM 24 TO 59 MONTHS AT BA TRI DISTRICT KINDERGARTEN, BEN TRE PROVINCE 2022-2023 - Trinh, Hoa Binh; Le, Thanh Tai; Pham, Thi Duong Nhi (Cantho Journal of Medicine and Pharmacy, 2023)
Background: Malnutrition is a major public health problem. The consequence is poor physical and intellectual development and long-term consequences in adulthood. According to the World Health Organization (WHO), by 2020, the world will have about 149 million children under 5 years old. Objectives: Determining the prevalence and severity of malnutrition among children aged 24-59 months and some factors related to malnutrition in preschools in Ba Tri district, Ben Tre province in 2022-2023. Material and methods: Cross-sectional study on 1036 children from 24 months to 59 months of age at kindergartens in Ba Tri district, Ben Tre province in 2022-2023. Results: The rate of underweight malnutrition was 2.5%, stunting malnutrition was 7.0%, emaciation malnutrition was 1.5% and the overall rate of malnutrition was 8.6%. Some factors related to malnutrition in children are the mother’s knowledge, the practice of choice of protein, starch, and vegetables, number of main meals for children and routine deworming habits for children (p<0.05). Conclusions: It is necessary to take measures to improve knowledge and improve practice for mothers of children from 24 months to 59 months of age to contribute to reducing the rate of malnutrition in children from 24 months to 59 months old.